2009
DOI: 10.2320/matertrans.mc200831
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Microstructure of Epitaxial Ti<SUB>3</SUB>SiC<SUB>2</SUB> Contact Layers on SiC

Abstract: Growth and microstructure of ternary Ti 3 SiC 2 compound layers on 4H-SiC, which play am important role in formation of TiAl-based ohmic contacts to p-type SiC, were investigated in this study. The Ti 3 SiC 2 layer was fabricated by deposition of Ti/Al contacts (where a slash ''/'' indicates the deposition sequence) on the 4H-SiC(0001) substrate and subsequent rapid thermal anneal at 1000 C in ultra high vacuum. After annealing, reaction products and microstructure of the Ti 3 SiC 2 layer were investigated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 20 publications
2
29
0
Order By: Relevance
“…This agrees with the {000l} morphology with {11 2 0} step facets that we observe in XRD and in the SEM images of our samples, as well as observations by Tsukimoto et al [9], on Ti 3 SiC 2 layers formed by high-temperature annealing of TiAl-based ohmic contacts on 4H-SiC.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…This agrees with the {000l} morphology with {11 2 0} step facets that we observe in XRD and in the SEM images of our samples, as well as observations by Tsukimoto et al [9], on Ti 3 SiC 2 layers formed by high-temperature annealing of TiAl-based ohmic contacts on 4H-SiC.…”
supporting
confidence: 93%
“…In such electronic device applications, a challenge is the formation of ohmic contacts to the SiC, as well as the durability of the contacts when operated at elevated temperatures. High-temperature annealed Ti/Al contacts on p-type SiC have been reported to form Ti 3 SiC 2 [5-8], which is suggested to contribute to the ohmic behavior of the contacts [9][10][11].Formation of Ti 3 SiC 2 and subsequent ohmic behavior has also been reported for hightemperature annealed Ti-based contacts on n-type SiC [12,13]. Here, we investigate the growth of Ti 3 SiC 2 thin films on 4° off-cut 4H-SiC using DC magnetron sputtering from three sources.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ti 3 SiC 2 is known to form after high temperature annealing of Ti-, and Ti/Albased contacts on SiC [6][7][8][9][10]. In recent publications, we have reported on the ohmic contact properties of sputter-deposited Ti 3 SiC 2 on 4H-SiC(0001), and investigated the step-flow growth mode of epitaxially grown Ti 3 SiC 2 layers on SiC [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…This topic is originated from the discovery of heteroepitaxial Ti3SiC2 formation at the interface of Ti/Al/4H-SiC and Ni/Ti/Al/4H-SiC after annealing at 1000 °C and 800 °C, respectively, which exhibited electrical Ohmic-contact behavior with low specific contact resistance [242]. Later, it has been reported that the Si-C-Si structure between the surface of SiC and the interfacial Ti3SiC2 has an important role of lowering Schottky barrier by intermediating the barrier height between the SiC substrate and the metal contact [243,244].…”
Section: From Interfacial Reaction To Substitution Reactionmentioning
confidence: 99%